In search of abnormal returns – measuring the performance of a contrarian value investment strategy in the Finnish stock market - Keskisarja, Ossi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Mean reversion, or the negative autocorrelation in the residuals of a return generating process is of significant economical interest whilst there are signs of overreaction in the stock market. It has been found in many past studies that over- or undervalued stock prices have a tendency to revert back to levels that reflect their long-term mean returns. Specifically, investors often exacerbate short-term market information. According to some, this creates a feasible investment opportunity over the longer term. Closely associated with over- and underreaction are the contrarian and momentum strategies, respectively. Contrarian strategy suggests buying past losers, while momentum strategy the past winners. Therefore contrarian investors expect a return reversal, as momentum investors believe in a return continuum. Based on the concept of mean reversion, overreaction and undervaluation, and motivated by the work of especially De Bondt & Thaler (1985), Chan (1988), Lo & MacKinlay (1990), Lakonishok et al. (1994), Dechow & Sloan (1997) and O'Hara et al. (2000), a new investment strategy, namely the contrarian value strategy was developed. In this thesis it was tested, along with the contrarian and momentum strategies, in the Finnish stock market during 2002–2012. Value-weighted monthly portfolio returns were calculated with rebalancing and reformatting the portfolios each year. The strategies' performances were then evaluated in several different ways; traditionally on a proportional cumulative return basis, against the market index, as well as on a risk-adjusted basis. Particularly it was examined whether abnormal returns in terms of alpha intercept were involved. For this purpose the market model of Black, Jensen and Scholes (1972) along with the three-factor model of Fama & French (1992–1993) was applied. Furthermore, the strategy returns were also adjusted for transaction costs and taxes to assess their economical significance. Although not too many studies exist covering the contrarian and momentum strategies' performance in the Finnish stock market, the results herein are in line with Grinblatt & Keloharju (2000) and Leivo & Pätäri (2011). The momentum strategy not only substantially outperforms the contrarian strategy over the test period, but additionally beats the market index by a clear margin. As for the contrarian value strategy, which screens for out of favor, yet still profitable as well as positive cash flow -generating companies, the results in the end are perhaps even surprising, given that the return continuum does seem to persist in Finland.